Rehabilitating sewerage line system in congested urban area - Daud, Mohd. Nor Siza (2015)
Since 1957, after Malaysia independent, there were only few proper sewerage systems because of low population density in urban area and not rapid urban developments. After 57 years of independent and in Malaysia heading to be a developed country by 2020, the restoration of good condition sewerage line system, it operation and maintenance is very important at urban area. There are challenges when the rehabilitation works for sewerage line system is carried out in developed area. In rapid development area for sewerage line, the space areas are very limited and congested. Besides many other utilities are sharing road services areas. The paper highlights the investigation of common problems occur installation of sewerage line system and propose suitable area for sewerage line system that will help designer in making decision to selecting sewerage line system alignment. Questionnaires were distributed to respondents in order to gain information of data collection. The feedbacks were analysed using descriptive analysis with the help of SPSS and excel in order to priorities the main problem in rehabilitation sewerage line system in congested urban area. This study found improvement in systematic sewerage rehabilitation planning in congested urban area, determination of effective rehabilitation methods and substitution pipe materials, improvement of construction methods and providing clean and fresh environment of surrounding area are the key factors in the justification of rehabilitation works of sewerage line system in urban area.